Comparison of MRCP and ERCP findings: a retrospective secondary data analysis - Farman Ali; Naveed Aamir; Muhammad Kamran Hassan; Fakhar-E-Alam; Hashmat Ullah Khan; Dilaram Khan (Journal of the Pakistan Medical Association, 2022)
Objective: To compare the findings of magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatographyin patients presenting with bile duct disorders. Methodology: The retrospective secondary-data study was conducted at the Gastroenterology Department of Lady Reading Hospital, Peshawar, Pakistan,and comprised data of patients who presented with bile duct disordersfrom June2019 to May2020. Data was analysed using SPSS 25. Results: Of the 92 patients, 41(44.6%) were males and 51(55.4%) were females. The overall mean age was 50.12 years with a standard deviation of 16.70 years (ranged: 13-80 years). Out of 28 bile duct calculi cases detected by endoscopic retrograde cholangiopancreatography, 25(89.3%) were detected by magnetic resonance cholangiopancreatography, and, of the 64 without calculi, it detected 50(78.1%). Out of 8 bile duct strictures detected by endoscopic retrograde cholangiopancreatography, 3(37.5%) were correctly diagnosed by magnetic resonance cholangiopancreatography, and, of the 84 unaffected patients, it excluded 79(94%). Out of 64 bile duct dilatation cases, magnetic resonance cholangiopancreatography correctly diagnosed 59(92.2%), and, of the 28 unaffected patients, it excluded 27(96.4%). Conclusion: For bile duct stone and dilation, magnetic resonance cholangiopancreatography was found to have high diagnostic accuracy. Key Words: Choledocholithiasis, Cholangiopancreatography, MRCP, ERCP. Continuous...